КОМБИНАТОР ТИЛШУНОСЛИК ТУШУНЧАЛАРИНИНГ БАЗАВИЙ ТИЗИМИ - Юнусова, Б.А. (SCIENCE and SOCIETY, 2021)
This article discusses the basic concepts of combinatorial linguistics: syntagmatics, combinatorics, position, connection, distribution, context, collocation, colligation, the categories of connection of words.
Keywords: cognitive linguistics; denotative meaning; connotative meaning; distribution; descriptive linguistics; collocation; colligation